Traversal Using Relays Around Nat by Coturn for Webrtc Systems - Raswa, Raswa; Lubis Ghozali, Ahmad; Adi Cahyanto, Kurnia (Journal of World Science, 2023)
Real-time communication between people in the form of audio, images, video, and data is now a necessity. Web Real-Time Communication Technology, WebRTC, is implemented as an open web standard and is available to build such communication. WebRTC requires a server that functions as both signaling and media servers. Signaling server for establishing communication channels, exchanging information, and synchronizing changes. Media servers exchange media, codecs, bandwidth, and rate control. Different Real-time Protocol (RTP) topologies have different requirements on servers, including those caused by the NAT configuration used. This research focuses on the role of the TURN server using CoTurn to create web-based real-time communication services. How is the quality of WebRTC service when CoTurn is a TURN server to pass signaling and media. The method used is divided into three stages, namely: (1) installation and configuration, (2) building WebRTC, and (3) testing. This study shows that real-time communication in the form of audio and video can be carried out even through a symmetrical NAT configuration. It is just that with more than five users in the WebRTC system, communication is slowing down. The proposed further research is developing and engineering the RTP topology to increase the number of users. The CoTurn application can be installed on a Virtual Private Server (VPS) and configured as a TURN Server as a media server service in the WebRTC system.